2015
DOI: 10.1002/2015gl066853
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide production by nitrification and denitrification in the Eastern Tropical South Pacific oxygen minimum zone

Abstract: The Eastern Tropical South Pacific oxygen minimum zone (ETSP‐OMZ) is a site of intense nitrous oxide (N2O) flux to the atmosphere. This flux results from production of N2O by nitrification and denitrification, but the contribution of the two processes is unknown. The rates of these pathways and their distributions were measured directly using 15N tracers. The highest N2O production rates occurred at the depth of peak N2O concentrations at the oxic‐anoxic interface above the oxygen deficient zone (ODZ) because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
179
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(211 citation statements)
references
References 71 publications
28
179
4
Order By: Relevance
“…3). Such a pattern has been previously reported for the ETSP (Farías et al, 2007) and similar systems with prominent OMZs (Bange et al, 2001;Bange et al, 2010), and it is generally ascribed to alternating activity of microbial N 2 O production-consumption pathways along the vertical O 2 gradients (Codispoti and Christensen, 1985;Ji et al, 2015). …”
Section: Depth Distribution Of N 2 Omentioning
confidence: 76%
“…3). Such a pattern has been previously reported for the ETSP (Farías et al, 2007) and similar systems with prominent OMZs (Bange et al, 2001;Bange et al, 2010), and it is generally ascribed to alternating activity of microbial N 2 O production-consumption pathways along the vertical O 2 gradients (Codispoti and Christensen, 1985;Ji et al, 2015). …”
Section: Depth Distribution Of N 2 Omentioning
confidence: 76%
“…Farías et al, 2009;Ji et al, 2015). During denitrification, the canonical reduction of nitrate to molecular nitrogen, N 2 O evolves as an intermediate product.…”
Section: Introductionmentioning
confidence: 99%
“…There is a strong indication that at low oxygen concentrations nitrification and denitrification may take place in close proximity (Kalvelage et al, 2011), and the N 2 O production and consumption under these conditions are strongly influenced by the interaction of both processes (Ji et al, 2015). Measurements of N 2 O consumption rates in the eastern tropical North Pacific Ocean (ETNP) furthermore provided evidence for a rapid N 2 O cycling, although depth profiles of N 2 O seemed to be relatively invariant over time .…”
Section: Introductionmentioning
confidence: 99%
“…N 2 O production is highest under nearly anoxic conditions, where oxygen concentrations restrain both nitrification (too little oxygen) and denitrification (too much oxygen). Both processes produce N 2 O, with a higher N 2 O yield in oxygen stress (Goreau et al, 1980;Patureau et al, 1994;Ji et al, 2015). In addition, when nitrifying microbes become oxygen limited, they too start to reduce NO − 2 to N 2 O (Poth and Focht, 1985;Wilson et al, 2014).…”
Section: N 2 O Dynamics In the Egbmentioning
confidence: 99%
“…The main biological pathways of N 2 O production are highly dependent on the oxygen conditions and the availability of organic matter, nitrite (NO − 2 ) and nitrate (Ward, 2013;Murray et al, 2015). In seas, nitrification has been considered the primary pathway of N 2 O production (Freing et al, 2012), but recent studies have suggested that the role of incomplete denitrification in the oceanic oxygen minimum zones might have been previously underestimated Ji et al, 2015). Furthermore, it has been shown that archaeal nitrification dominates oceanic N 2 O production and that this is much more sensitive to oxygen concentrations than bacterial nitrication (Löscher et al, 2012;Freing et al, 2012).…”
mentioning
confidence: 99%